2011
DOI: 10.1590/s1517-83822011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the pathogenicity of seabed isolates of Fusarium equiseti and the effect of the composition of the mineral salt medium and temperature on mycelial growth

Abstract: The pathogenicity of seven strains of Fusarium equiseti isolated from seabed soil was evaluated on different host plants showing pre and post emergence damage. Radial growth of 27 strains was measured on culture media previously adjusted to different osmotic potentials with either KCl or NaCl (-1.50 to -144.54 bars) at 15º, 25º and 35º C. Significant differences and interactive effects were observed in the response of mycelia to osmotic potential and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…Previous studies have shown that the patterns of fungal growth and toxin biosynthesis in the pathogenic and mycotoxigenic Fusarium verticillioid.es, Fusarium proliferation and Fusarium graminearum are consistent with their occurrence within Europe and especially in Spanish cereal fields (Jurado et al, 2008;Marin et al, 2010aMarin et al, , 2010b. The effect of water potential and temperature on fungal growth, trichothecene production and pathogenicity was reported previously (Kosiak et al, 2005;Marin et al, 2012;Palmero et al, 2011). However, there are no studies that link these data at a fundamental level to expression of key regulatory genes such as TRI5 in the case off.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies have shown that the patterns of fungal growth and toxin biosynthesis in the pathogenic and mycotoxigenic Fusarium verticillioid.es, Fusarium proliferation and Fusarium graminearum are consistent with their occurrence within Europe and especially in Spanish cereal fields (Jurado et al, 2008;Marin et al, 2010aMarin et al, , 2010b. The effect of water potential and temperature on fungal growth, trichothecene production and pathogenicity was reported previously (Kosiak et al, 2005;Marin et al, 2012;Palmero et al, 2011). However, there are no studies that link these data at a fundamental level to expression of key regulatory genes such as TRI5 in the case off.…”
Section: Introductionsupporting
confidence: 68%
“…These include cereals, wheat, triticale, maize, oat and rice, participating as a minor component of the Fusarium head blight (FHB) disease complex (Kosiak et al, 2003;Logrieco et al, 2003;Xu et al, 2008). Other susceptible crops are asparagus, cotton, potato, tomato, cowpea, onion, bean, bush bean, broad bean, chickpea, pea, alfalfa, canola, kohlrabi, melon and ginseng (Palmero et al, 2011;Punja et al, 2008). Besides cultivated plants, it also colonizes wild species, including herbal plants and trees, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…19 This might be due, at least in part, to the availability of osmolytes synthesized by the fungus that alleviate the saline stress and, therefore, increases its osmotolerance. 4 In vitro assays performed by Palmero et al 32 showed that the colony diameter of F. equiseti exposed to NaCl concentrations was similar to that observed in LPSC 1002, but lesser than that from LPSC1001. In higher NaCl concentrations the growth of LPSC 1002 was higher than those reported for F. equiseti.…”
Section: Discussionmentioning
confidence: 87%
“…showed that conidial germination in F. solani and F. equiseti was positively affected by the decrease of osmotic potential of the aqueous medium. 32 El-Abyad et al 8 also found that the addition of salt to the media increased mycelial growth and/or conidial germination of F. avenaceum, F. culmorum, F. diversisporum, F. equiseti and F. oxysporum f. sp.betae, but reduced also the growth rate in F. verticillioides. In contrast to our results, typical water molds that commonly infect eggs and adults of fish such as the members of the Saprolegniaceae family are not tolerant to saline conditions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation